Non-binary language in consecutive interpreting from English into Italian: An experimental study on the viability of schwa endings - Facchini, Igor; Torresi, Ira (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2024)
Italian is a gender-marked binary language with masculine and feminine as the only possible grammatical genders. One strategy that was recently put forward to deconstruct the gender dichotomy and to allow for non-binary individuals to be linguistically acknowledged is to replace gendered endings (-a,-o,-e,-i) with a schwa (ə), both in writing and speech. While some authors and media outlets have started adopting this solution in written texts, questions may arise concerning its viability in the oral medium, particularly in constrained translation modes such as conference interpreting. If, on the one hand, the schwa could serve as a less time-consuming alternative to extended gender-neutral periphrases, on the other, such benefit may be outweighed by processing capacity overloads, since non-binary schwa declensions entail morphological changes that are non-standard in spoken Italian, and may thus prove too burdensome to control. In order to investigate this issue, an experimental study was conducted with 12 advanced trainee interpreters who were instructed to interpret consecutively a text from English into Italian using schwa endings when referring to humans. Although with a certain amount of non-fluencies, misuse of schwa endings and occasional relapse into binary language, participants were mostly able to implement effective non-binary language strategies.